Skills for the Labor Market in Indonesia : Trends in Demand, Gaps, and Supply - di Gropello, Emanuela; Kruse, Aurelien; Tandon, Prateek (World Bank, 2012)
Creating jobs and increasing productivity are key concerns for policy makers across the globe. For East Asian countries seeking to reduce poverty, expanding employment and productivity is at the top of the agenda. This book is a comprehensive look at the demand and supply of skills in Indonesia how skills have changed, how they will continue to evolve, and how the education and training sectors can be improved to be more responsive and relevant to the needs of the labor market and the economy as a whole. Using an innovative firm survey, the authors shed light on the functional skills that workers must possess to be employable and to support firms' competitiveness and productivity. They also assess the role of the education and training systems in providing those skills. Although this book focuses specifically on Indonesia, its methodologies, messages, and analysis will be instructive for researchers and policy makers who shape the delivery of education and training in other middle-income countries around the world.